#### Answer

$\dfrac{5x-20}{3x^{2}+x}\cdot\dfrac{3x^{2}+13x+4}{x^{2}-16}=\dfrac{5}{x}$

#### Work Step by Step

$\dfrac{5x-20}{3x^{2}+x}\cdot\dfrac{3x^{2}+13x+4}{x^{2}-16}$
Factor both rational expressions completely:
$\dfrac{5x-20}{3x^{2}+x}\cdot\dfrac{3x^{2}+13x+4}{x^{2}-16}=\dfrac{5(x-4)}{x(3x+1)}\cdot\dfrac{(x+4)(3x+1)}{(x+4)(x-4)}=...$
Evaluate the product of the two rational expressions and simplify by removing the factors that appear both in the numerator and the denominator of the resulting expression:
$...=\dfrac{5(x-4)(x+4)(3x+1)}{x(x+4)(x-4)(3x+1)}=\dfrac{5}{x}$